PERAN FINTECH DALAM MEMODERASI PENGARUH PENGUNGKAPAN RISIKO KEUANGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - Alexandra Christina Rattu; Faisal Faisal (Diponegoro Journal of Accounting, 2026)
This study aims to obtain empirical evidence regarding the effect of financial risk disclosure on financial performance, as well as the moderating role of FinTech Adoption in banking companies listed on the Indonesia Stock Exchange (IDX). The sample was determined using the purposive sampling method and consisted of 40 conventional commercial banks during the 2020–2023 period, resulting in a total of 160 observations. The research data were obtained from the annual reports of the banking companies.This study employed a quantitative method using multiple linear regression analysis and Moderated Regression Analysis (MRA). The independent variable in this study was financial risk disclosure, the dependent variable was financial performance, and FinTech Adoption served as the moderating variable. This study also used control variables, namely firm size, leverage, external regulation, and audit quality.The results indicate that financial risk disclosure does not have a significant effect on banks’ financial performance. FinTech Adoption was proven to significantly moderate the relationship between financial risk disclosure and financial performance with a negative direction, thereby weakening the relationship. Among the control variables, leverage has a negative and significant effect, while audit quality has a positive and significant effect on financial performance. These findings indicate that financial risk disclosure has not yet become a sufficiently strong factor in improving banks’ financial performance, while a high level of FinTech adoption may increase information complexity, exposure to new risks, and pressure on profitability, thereby reducing the effectiveness of risk disclosure in improving financial performance. This study provides empirical evidence regarding the moderating role of FinTech in the relationship between financial risk transparency and financial performance in Indonesia’s banking sector.